Synthesis, comparative docking, and pharmacological activity of naproxen amino acid derivatives as possible anti-inflammatory and analgesic agents - Elhenawy AA; Al-Harbi LM; Moustafa GO; El-Gazzar MA; Abdel-Rahman RF; Salim AE (Dove Medical Press, 2019)
Ahmed A Elhenawy,1 LM Al-Harbi,2 Gaber O Moustafa,3 MA El-Gazzar,1 Rehab F Abdel-Rahman,4 Abd Elhamid Salim11Chemistry Department, Faculty of Science, Al-Azhar University (Boys’ Branch), Nasr City, Cairo, Egypt; 2King Abdulaziz University, Jeddah 21589, Saudi Arabia; 3Peptide Chemistry Department, Chemical Industries Research Division, National Research Centre, Dokki, Giza 12622, Egypt; 4Department of Pharmacology, National Research Centre, Giza, EgyptBackground and aim: Naproxen is a member of the Nonsteroidal anti-inflammatory drugs (NSAIDs). This work aimed to synthesize a safe NSAID agent based on a peptide derivative.Methods: The structure of compounds 5–20 was established on the basis of spectral data. Frontier molecular orbitals and chemical reactivity were discussed to clarify inter- and intramolecular interactions among tested compounds. We applied competitive molecular docking using polynomial logarithms to identify the most accurate algorithm for pharmacological activity prediction for the tested compounds. The docking protocol with the lowest RMSD was selected for analyzing binding affinity.Results: Docking results illustrated that the binding interaction increased after introduction of an acidic fragment to the parent compound. These compounds were selected for additional study against adsorption, distribution, metabolism, excretion, and toxicity (ADMET) in silico. The compounds tested had good oral bioavailability without any carcinogenesis effect; no marked health effects were observed via rodent toxicity. Compounds passed through docking and ADMET profiles for them (5–16) were examined as anti-inflammatory and analgesic agents. Compounds 8 and 16 showed higher anti-inflammatory potency than the reference drug and tested compounds. Compounds 8, 10, and 14 exhibited the highest analgesic potency compared to the other tested compounds.Conclusion: The tested compounds have shown negligible ulcerogenic effects, and may be considered safer drugs than naproxen for treating inflammatory conditions.Keywords: naproxen, isothiocyanate, peptide candidates, anti-inflammatory and analgesic agents, docking